A Combined Upper-Sided Synthetic S2 Chart for Monitoring the Process Variance. (24th June 2020) - Shan, Tingting; Wu, Liusan; Hu, Xuelong
Abstract : In order to monitor the process variance, this paper proposes a combined upper-sided synthetic S 2 chart for monitoring the process standard deviation of a normally distributed process. This combined upper-sided synthetic S 2 chart comprises a synthetic chart and an upper-sided S 2 chart. The design and performance of the proposed chart are presented, and the steady-state average run length comparisons show that the combined upper-sided synthetic S 2 chart outperforms the standard synthetic S 2 chart as well as several run rules S 2 charts, especially for larger shifts in the process variance.